Inclusiveness Of Islamic Studies West and East (International Journal of Education and Literature, 2023)
This article shows a methodological study of Islamic Studies in the West and East. Even though they both study Islam, there are distinctive characteristics of each study period that result in gaps between the two. This paper is intended to answer the questions (1) How is the concept of Islamic studies in the West and East (2) How is the inclusiveness of Islamic studies in the West and East. (3) How is the inclusiveness of Islamic studies in the West and East. This problem is discussed through library research studies. All data was analyzed descriptively focusing on a systematic explanation of the facts obtained during the research. The results of the analysis and conclusions show that Islamic stIdui in the west and east have their own characteristics. Studies in the West have an anthropocentric pattern, while Islamic studies in the East have a theocentric pattern. Both regional studies in the west and east have their own inclusiveness. Both must remain true to their respective characteristics to strengthen each other. Sometimes harmony is found, while Western Islamic studies research can strengthen Eastern Islamic studies with its scientific basis. Of course, these findings can provide a reference for Islamic studies that are always fresh to be discussed in order to add to the Islamic treasures throughout the world.